2018
DOI: 10.3390/ma11091630
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Surrounding Ring of Two Different Extra-Short Implant Designs in Crestal Bone Maintanence: A Histologic Study in Dogs

Abstract: The aim of this study was to compare the implant stability and bone resorption and formation of two different extra-short implant designs with different diameter rings placed in a dog´s maxilla. Thirty-six extra-short, 5 mm diameter × 4 mm length (Short DM®, Bioner Sistemas Implantológicos, Barcelona, Spain), delayed implants were placed in each hemimaxilla of six dogs at the bone crest level. Eighteen implants of each design (wide and narrow ring) were installed. After 8 and 12 weeks of healing, histomorphome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Several studies about implant neck design and marginal bone loss can be found in the literature, but the results are controversial. In vivo animal studies reported a greater crestal bone height and thickness of surrounding implant tissue in dental implants with triangular neck designs [8]; smaller crestal bone loss but similar peri-implant tissue thickness in narrow ring extra-shorts implants [9]; and greater bone loss in dental implants with micro-rings on the neck, as compared to open-thread implant collars [10]. Human model studies reported improved biomechanical behavior for stress/strain distribution pattern in dental implants with divergent collar design [11]; no additional bone loss in non-submerged dental implants with a short smooth collar compared to similar but longer implant collar design [12].…”
Section: Introductionmentioning
confidence: 98%
“…Several studies about implant neck design and marginal bone loss can be found in the literature, but the results are controversial. In vivo animal studies reported a greater crestal bone height and thickness of surrounding implant tissue in dental implants with triangular neck designs [8]; smaller crestal bone loss but similar peri-implant tissue thickness in narrow ring extra-shorts implants [9]; and greater bone loss in dental implants with micro-rings on the neck, as compared to open-thread implant collars [10]. Human model studies reported improved biomechanical behavior for stress/strain distribution pattern in dental implants with divergent collar design [11]; no additional bone loss in non-submerged dental implants with a short smooth collar compared to similar but longer implant collar design [12].…”
Section: Introductionmentioning
confidence: 98%
“…Extra-short dental implants have nowadays survival rates similar to conventional dental implants when the number of dental implants and the antagonist are optimal [16,17,18,19,20]. The purpose of this study was to perform a finite element analysis to compare stress distribution in two extra-short dental implants with different connections (HI and MT) with a load of 150 N axial and an oblique load of 30°.…”
Section: Introductionmentioning
confidence: 99%